Promoting the Benefits and Clarifying Misconceptions about Preregistration, Preprints, and Open Science for the Cognitive Science of Religion. (9th September 2020) - Kavanagh, Christopher; Kapitany, Rohan
Abstract : Adopting newly proposed "open science" reforms to improve transparency and increase rigor is hard and can make us, as researchers, feel vulnerable. Nonetheless, these reforms are vital to improving the overall quality and confidence of our collective research. We have, through  our own experiences, found that preregistration and detailed analysisplans can help to identify, and potentially avoid, errors. Prepublication has similarly helped us to collaborate and receive feedback on manuscripts, particularly during prolonged periods of peer-review. The Cognitive Science of Religion (CSR) field is constituted by a diversity of scholars and disciplines, and thus faces somewhat unique challenges in its efforts to establish common practices, standards, and research terminology. In this paper we offer an introduction to the open science reforms of preregistration and prepublication specifically orientated towards the CSR field. We discuss common concerns around these practices, highlighting areas of misunderstanding while conceding and discussing genuine limitations. We conclude with voluntary, low-investment recommendations for best-practices with regards to preregistration and preprints for the field of the Cognitive Science of Religion.